Synergy between Sustainable Development and Digital Transformation: A Scientific Approach - Iris Jiménez–Pitre; Fabio Orlando Moya Camacho; Ca Socarrás-Bertiz (Kurdish Studies, 2024)
A documentary review was carried out on the production and publication of research papers related to the study of the Sustainable Development and Digital Transformation variables. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022 by Latin American institutions, achieving the identification of 80 publications. The information provided by this platform was organized through graphs and figures, categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors on the proposed topic is referenced through a qualitative analysis. Among the main findings made through this research, it is found that Brazil, with 45 publications, was the Latin American country with the highest scientific production registered in the name of authors affiliated with institutions of that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material related to the study of the Sustainable Development and Digital Transformation variables was Social Sciences with 32 published documents, and the most used Publication Type during the period indicated above were Journal Articles with 46% of the total scientific production.